Compreensão de currículo na educação profissional: possibilidades e tensões do ensino médio integrado - Hannecker, Lenir Antonio (Universidade do Vale do Rio dos Sinos, 2014)
The possibilities and tensions that permeate the Integrated Education in Technical Course in Agropecuária IFRS, Campus Sertão, constitute the object of this study, in order to better understand its implementation and development. In a school context historically marked by alternate ways to develop the professional middle-level education, sometimes concurrent, sometimes integrated, we investigated whether the Integrated Education contributes to better vocational training students of education. For this we collect the opinion of teachers, administrative staff and students, comparing the two types of course happening on campus: the Headquarters Unit, writh presence, focusing on Traditional Agropecuária and the Polo Pontão Unit, writh Pedagogy of Alternation with emphasis on Agroecology. Through an examination between two modes of curricular achievement was possible to notice that rare moments of discussion and planning had the chance in the development and implementation of Integrated syllabus in both contexts, motivated mainly because the proposal wasn’t Born of the collective will of the school community, but by administrative guidance to the Federal Network. Many authors have enriched the study and analysis about Integrated Syllabus, as Basil Bernstein, Boaventura de Sousa Santos, James Beane, Edgar Morin, Maria Isabel da Cunha, Maria Ciavatta, Antonio Nóvoa and MauriceTardif and warned about the importance of continuous reflection on the organization of syllabuses, teaching activities, everybody availability necessary for collective planning, including the renewed discussion of methodologies to teach and to integrate value and appreciation of the students . To better know the data, we established three organizational dimensions : personal and subjective conditions of those involved; conditions of professionalism and knowledge and the conditions of structuring and organization of work. We admited that the process student’s formation pass by teacher training and there is, in this context, need for appreciation of scientific knowledge and knowledge of common sense, including an ongoing dialogue among teachers, students and the sociocultural reality. We believe that education presupposes autonomous learning including aspects of intellectual, emotional and moral. We admited that the syllabus isn’t only a contents list, but a process of constant tensions and doings. Therefore, changing the syllabus proposal involves considering the conception of knowledge involved. In the study, it was motived that although there is successful interdisciplinary practices in both situations investigated, the Pedagogy of Alternation favors the achievement of better results in integrated curricular activities, especially the most intense relationship of students with professional practices in time Community. There's conscience, part of the most of informers, that the Integrated Syllabus effectively articulates and produces new knowledge, gives opportunity to associate previous knowledge and appreciation of students' experiences, avoids overlapping contents, and encourages the student to think, because closer theory and practice leads to better training of students. However recognize that there are epistemological and structural difficulties in its implementation and would be required an institutional investment for its implementation.
Keywords: Cursos Técnicos; Educação profissional; Currículo Integrado; Pedagogia da Alternância; Inter e transdisciplinaridade; Technical Courses; Professional education; Integrated Syllabus; Pedagogy of Alternation; Inter and transdisciplinary; ACCNPQ::Ciências Humanas::Educação